2009
DOI: 10.1111/j.1600-0501.2008.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of voxel values in mandibular cancellous bone: relationship between cone‐beam computed tomography and multislice helical computed tomography

Abstract: It was suggested that voxel values of mandibular cancellous bone in cone-beam CT could be used to estimate bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 10 publications
4
89
0
3
Order By: Relevance
“…Therefore, the presence of high‐ or low‐density materials in the FOV can affect the distribution of voxel values. Similar findings were reported by Bryant et al ( 12 ) In contrast to the current results, Lagravère et al ( 15 ) and Naitoh et al ( 17 ) have stated that a linear conversion can be made between density measurements on a CBCT scan and CT numbers. Furthermore, density measurements were independent of the position in the volume.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the presence of high‐ or low‐density materials in the FOV can affect the distribution of voxel values. Similar findings were reported by Bryant et al ( 12 ) In contrast to the current results, Lagravère et al ( 15 ) and Naitoh et al ( 17 ) have stated that a linear conversion can be made between density measurements on a CBCT scan and CT numbers. Furthermore, density measurements were independent of the position in the volume.…”
Section: Discussionsupporting
confidence: 91%
“…However, a number of studies have already assessed technical image quality for one or more CBCT devices, using an existing commercial quality control (QC) phantom, ( 8 , 9 ) a phantom provided by a CBCT manufacturer, ( 2 , 10 ) a water phantom, ( 8 , 11 ) a customized test object, ( 12 15 ) or clinical data. ( 16 , 17 ) Although these studies have provided useful insights regarding certain image quality aspects, they also show the need for a standardized QC phantom that is suited for use on all CBCT devices, and which provides results that are relevant to dental imaging and that can be compared between systems. Commercial QC phantoms have been described for conventional CT, but these are not applicable for dental CBCT due to the difference in performance for certain image quality aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The voxel value on CBCT is not an absolute value, unlike the CT value on systemic CT, but it is a relative value representing bone density. 18 When segmentation of an object is performed with different thresholds, the threshold values must be changed. 19 For example, since the bone density is low and multiple bones overlap in the mandibular head region, segmentation is more difficult than in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, (Katsumata et al, 2007), the authors found that calculated HU on a CBCT scan varied widely from a range of -1500 to over +3000 for different types of bone. However, after a correction has been applied to grey levels with the CBCT, the HU values are much similar to those one would expect in a medical CT device than to the original grey levels obtained from the CBCT scanners (Naitoh et al 2009;Nomura et al, 2010, Mah et al, 2010. The clinical utility of preoperative implant planning by use of in imaging stent that helps relate the radiographic image and its information to a precise anatomic location or a potential implant site.…”
Section: Cone-beam Computed Tomographymentioning
confidence: 62%
“…Both CT and CBCT images provide information on the continuity of the cortical bone plates, residual bone in the mandible and maxilla, the relative location of adjoining vital structures and the contour of soft tissues covering the osseos structures (Benson & Shetty, 2009;Scarfe & Farman, 2008). Voxel values obtained from CBCT images are not absolute values, like HU values obtained using CT, various methods have been proposed to evaluate the bone density (Naitoh et al 2009;Mah et al, 2010). HU provide a quantitative assessment of bone density as measured by its ability to attenuate an x-ray beam.…”
Section: Cone-beam Computed Tomographymentioning
confidence: 99%